Upaya Meningkatkan Kemampuan Komunikasi Matematika Siswa Menggunakan CTL di MTS Nurul Hakim Tembung - Hizmi Wardani (Universitas Muslim Nusantara Al Washliyah, 2018)
Abstract This study aims to determine: (1) Improvement of students' math communication skills taught by using CTL is better than students who are taught using PB. This study is a quasi experiment. The experimental design used in this research is pretest posttest contro group design. Variable in this research consist of independent variable that is CTL and ordinary learning, while dependent variable that is communication ability. The sampling technique is purposive sampling. The instrument in this study consisted of the test of mathematical communication ability. athematical communication ability tests were analyzed using inference analysis of anava. Based on the results of the research, it is known that: (1) the calculation result using two path Anava is 0,00